Pelatihan Akuntansi Berbasis Masjid Pemuda Masjid di Kelurahan Bedahan Sawangan, Depok (Neolectura, 2020)
Bedahan Village is one of the villages in the Sawangan sub-district of Depok where the religious atmosphere (Islam) is very thick. This shows that the undisturbed villages are predominantly Muslim. Bedahan Village has eight mosques. Based on information from the BKPM (Mosque Youth Communication Agency), mosque financial management has not been carried out properly, where the mosque does not yet have reception and expenditure accounts. All receipts are put together as well as their use to finance all mosque activities put together into an expense account. BKPM which is a mosque-based youth organization intends to conduct training with the theme: